Dangerous girls and cheating boys: Zulu-speaking disabled young peoples' constructs of heterosexual relationships in Kwazulu-Natal, South Africa. Issue 5 (4th May 2017) - Chappell, Paul
Abstract: Across South Africa there is a growing body of work that explores gender dynamics in heterosexual relationships between young people aged 15–24 years. This is mainly influenced by the high prevalence of HIV and the incidence of intimate partner violence in this age group. Most studies to date have been based upon non-disabled young people, with limited focus on young disabled people. In an attempt to address this gap, this paper describes findings from a study conducted with 22 Zulu-speaking young people with visual and physical disabilities in KwaZulu-Natal. Throughout the findings, young disabled participants appeared to downplay their disability with respect to intimate relationships and accentuated the interweaving of complementary and contentious discourses of gender and cultural identity. Taking cognisance of the intersectionality of gender and cultural discourses, the paper extend constructs of disabled sexualities beyond an exclusive gaze on disability in the South African context.